2009
DOI: 10.1093/bioinformatics/btp423
|View full text |Cite
|
Sign up to set email alerts
|

Using a mutual information-based site transition network to map the genetic evolution of influenza A/H3N2 virus

Abstract: All code and data are available at http://ibi.zju.edu.cn/birdflu/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…We demonstrated that the informatics framework PREDAC we developed can effectively infer antigenic clusters from HA sequences, and thus can provide a very important tool in the influenza surveillance and vaccine strain recommendation when coupled with large-scale HA sequencing. Previously, many computational approaches were designed to either predict antigenic variants 18,[30][31][32][33][34][35][36] or to model evolutionary patterns for the H3N2 virus [19][20][21]23,24 . In our study, the prediction of antigenic variants and the modeling of antigenic evolutionary patterns are integrated into one computational framework, PREDAC.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the informatics framework PREDAC we developed can effectively infer antigenic clusters from HA sequences, and thus can provide a very important tool in the influenza surveillance and vaccine strain recommendation when coupled with large-scale HA sequencing. Previously, many computational approaches were designed to either predict antigenic variants 18,[30][31][32][33][34][35][36] or to model evolutionary patterns for the H3N2 virus [19][20][21]23,24 . In our study, the prediction of antigenic variants and the modeling of antigenic evolutionary patterns are integrated into one computational framework, PREDAC.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the MI has already been applied to study the genetic drift of influenza A/H3N2 virus [28]. The MI concept is useful when analyzing symbolic RNA or DNA sequences.…”
Section: Introductionmentioning
confidence: 99%
“…With entropy, a simple informational index was proposed in [17] to reveal the patterns of synonymous codon usage bias. Further, mutual information was utilized in the construction of site transition network based on 4064 HA1 of A/H3N1 sequences from 1968 to 2008, which was able to model the evolutionary path of the influenza virus and to predict seven possible HA mutations for the next antigenic drift in the 2009-2010 season [18]. Recently, entropy and mutual information were also applied to indentify critical positions and co-mutated positions on HA for predicting the antigenic variants [19].…”
Section: Introductionmentioning
confidence: 99%